Daya Saing Ketahanan Pangan Melalui Identifikasi Sikap Kepercayaan Konsumen Remaja Terhadap Produk Makanan Cepat Saji (Fast Food) dan Makanan Lokal (Tradisional) - Sentot, Sudiyarto (Jurnal Riset Ekonomi dan Bisnis, 2009)
Consumers especially the youngest trending to follow global life style and modern have freedom to choice the product when there buying, Therefore the grand problem when happened in Indonesian’s marketer and also food producer are incapability to provide it how did fulfill consumer behaviour local food that take competition from many kind of fast food. This research purposely firstly to analyze factors that influence consumer within buy or consumption fast food and local food. Secondly, to analyze competitive advantage with consumers attitude-trust approach toward attribute of fast food and local food, This research are using Fishbein Methods. The result it show local food have competitive advantage compares fast food.Keywords: Competitive Advantage, Consumers Behaviour, Food Product